STATE ADMINISTRATIVE COURT AND THE PROTECTION OF RELIGIOUS HUMAN RIGHTS THROUGH GOOD GOVERNANCE PRINCIPLES - Richella, Audrianna; Darmawan, Christian Indra; Jesslyn, Michelle (EKSEKUSI, 2026)
ABSTRACT This study examines the effectiveness of the State Administrative Court (Peradilan Tata Usaha Negara/PTUN) in protecting religious human rights through the application of good governance principles (AAUPB). The urgency of this research lies in the gap between normative legal guarantees and empirical realities, particularly when final and binding court decisions (inkracht) are not implemented. This study analyzes the role of PTUN and the factors behind the ineffectiveness of its decisions. Using a qualitative literature-based approach, this research reviews legal doctrines, regulations, and cases such as GKI Yasmin and HKBP Filadelfia. The findings show that PTUN decisions are often hindered by maladministration, legal evasion, and administrative resistance, including delays and contradictory actions. Structural limitations and socio-political pressures further weaken enforcement. In conclusion, the protection of religious human rights remains largely formal. Strengthening enforcement mechanisms and consistent application of AAUPB are necessary to ensure effective legal protection. Keywords: State Administrative Court, Maladministration, Legal evasion, Religious human rights ABSTRAK Penelitian ini mengkaji efektivitas Peradilan Tata Usaha Negara (PTUN) dalam melindungi hak asasi manusia di bidang kebebasan beragama melalui penerapan Asas-Asas Umum Pemerintahan yang Baik (AAUPB). Urgensinya terletak pada kesenjangan antara hukum secara normatif dengan realitas, khususnya ketika putusan pengadilan yang telah berkekuatan hukum tetap (inkracht) tidak dilaksanakan. Penelitian ini menganalisis peran PTUN serta faktor penyebab tidak efektifnya putusan. Metode yang digunakan adalah kualitatif dengan studi kepustakaan melalui analisis doktrin hukum, peraturan, dan kasus GKI Yasmin serta HKBP Filadelfia. Hasil menunjukkan bahwa putusan PTUN sering terhambat oleh maladministrasi, penyelundupan hukum, dan resistensi administratif seperti penundaan dan kebijakan yang bertentangan, serta diperparah oleh faktor struktural dan sosial-politik. Kesimpulannya, perlindungan HAM masih bersifat formal. Diperlukan penguatan eksekusi putusan dan penerapan AAUPB secara konsisten agar hukum berjalan efektif. Kata Kunci: Peradilan Tata Usaha Negara, Maladministrasi, Penyelundupan hukum, Hak asasi manusia